Respuesta :

fichoh

Answer: x = - 3.5

Step-by-step explanation:

Rewrite the equation by completing the square.

4x2 + 28x + 49 = 0

Completing the square method :

Divide through by the Coefficient of x^2

x^2 + 7x + (49/4) = 0

a = 1, b = 7, c = 49/4

Move c to the right side of the equation

x^2 + 7x = - 49/4

Complete the square on the left hand side by squaring its half of the x term

(7/2)^2 = (49/4)

Add the output to both sides of the equation

x^2 + 7x + (49/4) = - (49/4) + (49/4)

(x + 7/2)^2 = 0

Square root of both sides

x + 7/2 = 0

x = - 7/2

x = - 3.5

ACCESS MORE